Assessing the benefits and harms of low-dose computed tomography screening for lung cancer. (December 2014) - Pinsky, Paul F
SUMMARY : The concept of using low-dose computed tomography (LDCT) for lung cancer screening goes back almost 25 years. In 2011, the National Lung Screening Trial (NLST) reported that LDCT screening significantly reduced mortality from lung cancer in a high risk population. This article evaluates the benefits and harms of LDCT screening, based largely on evidence from randomized trials. Harms include false-positive screens and resultant diagnostic procedures, overdiagnosed cancers, and radiation exposure. Benefits can be expressed as the number needed to be screened to prevent one lung cancer death or as estimated overall reductions in lung cancer mortality assuming LDCT population screening as recommended by guidelines. Indirect metrics of benefit, such as lung cancer survival and stage distribution, as well as measures of harms, will be important to monitor in the future as LDCT screening disseminates in the population.